Financial Technology and Sharia Economic Empowerment in Indonesia: A Qualitative Study from a Digital Economy Perspective - Erizal Candra Efendi; Roni Andespa; Almizan Almizan (Al-bank: Journal of Islamic Banking and Finance, 2026)
This study examines the contribution of digital Sharia fintech to Islamic economic transformation and community economic empowerment in Indonesia. Although Islamic financial literacy and inclusion have improved, access to Sharia-compliant financial services remains lower than conventional finance. This study employed a descriptive qualitative approach using in-depth interviews with 15 purposively selected participants, including four Sharia fintech stakeholders, five MSME owners, three regulators, and three platform users in Jakarta, Bandung, and Yogyakarta. Interview data were complemented by official reports and relevant academic literature and analysed thematically through data reduction, data display, and conclusion drawing. The findings indicate that participants perceived Sharia P2P lending, profit-sharing crowdfunding, and e-waqf as accessible alternatives because they provide faster application procedures, transparent transactions, and financing mechanisms consistent with Sharia principles. MSME participants reported that fintech financing supported working capital and business expansion, while platform users emphasized transparency and Sharia compliance as key sources of trust. However, limited digital literacy, uneven internet infrastructure, insufficient product socialisation, and inadequate post-financing business mentoring remain barriers, particularly in rural areas. The study concludes that digital Sharia fintech can strengthen financial inclusion and community economic empowerment when supported by digital literacy, adaptive regulation, effective business mentoring, and collaboration among government, financial institutions, fintech providers, and local communities